Renal artery infarction in the SARS-Cov-2 era: A systematic review of case reports - Kozyrakis, Diomidis; Kallinikas , Georgios; Zarkadas , Anastasios; Bozios , Dimitris; Konstantinopoulos , Vasileios; Charonis , Georgios; Safioleas , Konstantinos; Filios , Athanasios; Rodinos , Evangelos; Mytiliniou , Despoina; Vlassopoulos , Gerasimos; Gkerzelis , Ioannis; et al. (Archivio Italiano di Urologia e Andrologia, 2023)
Aim: Renal artery infarction (RI) is the presence of blood clot in the main renal artery or its branches causing complete or partial obstruction of the blood supply. Its etiology is either related with disorders of the renal vasculature or with cardiovascular diseases. Recently, the SARSCoV- 2 virus is an emerging cause of thromboembolic events and the incidence of RI is anticipated to increase after the pandemic. Methods: A systematic review based on COVID-19 associated RI was conducted. Protocol: A systematic review of the Medline/Pubmed and Scopus databases was conducted in accordance to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (the PRISMA statement). Search strategy and information sources: A hand-search was performed using the terms “SARS-Cov-2” OR “COVID-19” AND “renal thrombosis” OR “renal infarction” OR “renal “thromboembolism”. Eligibility criteria: all types of publications (case reports, case series, letters to the editor, short communications) were evaluated for relevance. Inclusion criteria were: confirmed SARS-Cov-2 infection irrespectively of the age, diagnosis of RI during or after the onset of viral infection, and exclusion of other potential causes of thromboembolic event except of SARS-Cov-2. Patients with renal transplantation were also considered. Study criteria selection: after checking for relevance based on the title and the abstract, the full texts of the selected papers were retrieved and were further evaluated. Duplicated and irrelevant cases were excluded. Any disagreement was resolved by consensus with the involvement of a third reviewer. Quality of studies: The assessment of the quality case reports was based on four different domains: selection, ascertainment, casualty and reporting. Each paper was classified as “Good”, “Moderate” and “Poor” for any of the four domains. Data extractions: Crucial data for the conduct of the study were extracted including: age, sex, time from SARS-Cov-2 infection till RI development, medical history, previous or current antithrombotic protection or treatment, laterality and degree of obstruction, other sites of thromboembolism, treatment for thromboembolism and SARS-Cov-2 and final outcome. Data analysis: methods of descriptive statistics were implicated for analysis and presentation of the data. Results: The systematic review retrieved 35 cases in 33 reports. In most cases, RI was diagnosed within a month from the SARSCov- 2 infection albeit 17 out of 35 patients were receiving or had recently received thromboprophylaxis. Right, left, bilateral and allograft obstruction was diagnosed in 7, 15, 8 and 5 patients respectively. 17 cases experienced additional extrarenal thromboembolism primarily in aorta, spleen, brain and lower limbs. Low molecular weight heparins (LMWH) (usually 60-80 mg enoxaparine bid) was the primary treatment, followed by combinations of unfractionated heparin and salicylic acid, apixaban and rivaraxaban, warfarin, acenocoumarol or clopidogrel. Kidney replacement therapy was offered to five patients while invasive therapies with thrombus aspiration or catheter directed thrombolysis were performed in two. Regarding the outcomes, five of the patients died. The total renal function was preserved in 17 cases and renal impairment with or without hemodialysis was recorded in 5 patients, two of them having lost their kidney allografts. Limitations: The majority of included studies are of moderate quality. The results and the conclusions are based on case-reports only and crucial data are dissimilarly presented or missing through the relevant publications. Conclusions: Thromboprophylaxis may not offer adequate protection against SARS-Cov-2 induced thrombosis. Most patients could be effectively treated with conservative measures, while in more severe cases aggressive treatment could be recommended. Implications of key findings: Therapeutic doses of LMWH could be considered for protection against RI in SARS-Cov-2 cases. Interventional treatment could be offered in a minority of more severe cases after carful balancing the risks and benefits.